Casual slaughters and accidental judgments : Canadian war crimes prosecutions, 1944-1948 - Brode, Patrick, 1950- (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 1997)
War crimes prosecutions create unique difficulties as civilian standards of law are applied to the extraordinary circumstances of war. Governments are often surprisingly hesitant to pursue war criminals. Patrick Brode has produced a fascinating study of such issues in Casual Slaughters and Accidental Judgments, a history of Canada's prosecution of war crimes committed during the Second World War. Brode illustrates the difficulties of applying law to a recently defeated enemy when the emotions and politics of war distort any sense of impartial justice. The trials also reveal much about the legal and diplomatic views that prevailed at the end of the war and demonstrate Canada's willingness to overcome its colonial past to defend its own interests on the international stage.